Deposition and characterization of silver nano-films by a novel solid liquid interface reaction technique (SLIRT) - Godbole, P. D.; Mitra, A.; Pasricha, R.; Mandale, A. B.; Patil, K. R. (Materials Letters, 2005)
Solid-liquid interface reaction technique (SLIRT) is used to deposit silver film on glass substrate. The solid film of silver nitrate is formed by modified spin coating method. This film is subsequently processed by dipping it in a reducing solution so as to initiate a reaction at the interface and ultimately transform it to totally silver film. In situ transformation of silver nitrate to silver is studied with respect to time spectrophotometrically. The characterization of silver film is done by various physicochemical techniques namely XRD, XPS, ED, TEM and UV visible spectroscopy. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Electron microscopy; Nano-Particles; solid-liquid interface reaction; thin film

Transport study on as-grown and cast films of electrogenerated poly(3-hexylthiophene) - Jiang, Xiaoqing; Harima, Yutaka; Patil, Rahul (Materials Letter, 2007)
Two kinds of poly(3-hexylthiophene) films with identical chemical compositions are prepared. One of the films is obtained by electropolymerization of 3-hexylthiophene (as-grown film) and the other is prepared by casting a solution dissolving the as-grown film (cast film). A clear difference is found in the mobility vs. doping level plots between the as-grown and cast films and its reason is discussed. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: mobility; poly(3-hexylthiophene); swelling; thin film; transport mechanism

H(2)S gas sensitive indium-doped ZnO thin films: preparation and characterization - Badadhe, Satish S.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2009)
High quality indium-doped ZnO (IZO) thin films (similar to 100 nm) have been deposited onto the glass substrates by using a conventional spray pyrolysis technique. Precursors such as zinc acetate, indium chloride with Brij-35 (polyoxyethylene lauryl ether) as a non-ionic surfactant were used. The morphology, crystal structure, elemental analysis and the gas response properties were investigated by using SEM, TEM, XRD, AFM and XPS techniques. The films show hexagonal wurtzite structure which reveal variations in (100). (00 2) and (10 1) intensities with indium doping. The crystallite size calculated by Scherrer formula was in the range of 30-50 nm. The SEM and AFM analysis show 50-70 nm sized grains, while the TEM confirms formation of grains by similar to 10nm sized particles. Their response towards various gases was measured at different operating temperatures and different levels of In-dopants. The 3 at% In-doped ZnO showed response as high as 13,000 for 1000ppm H(2)S at 250 degrees C. It exhibited fast response (similar to 2s) and recovery time (similar to 4 min). The gas response strongly depends on the morphology and indium concentration. The high gas response of IZO is explained on the basis of thickness dependent trap state density. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Hydrogen sulfide sensor; Indium oxide; Spray pyrolysis; thin film; Zinc oxide

Fabrication of homogeneous nanoparticle/nanoneedle BaTiO3 and Ba0.8Sr0.2TiO3 smooth thin films by simple dip coating - Saini, Mamta; Vivekanand, K.; Poddar, Pankaj; Murty, K. V. G. K.; Thushara, K. S.; Gopinath, Chinnakonda S. (International Journal of Nanotechnology, 2010)
Ferroelectric BaTiO3 (BTO) and Ba0.8Sr0.2TiO3 (BSTO) thin film materials have been successfully prepared by sol-gel processing and simple dip coating on glass and silicon supports. Above thin films were characterised by x-ray diffraction (XRD), Raman spectroscopy, photoelectron spectroscopy, thermal analysis, atomic force microscopy (AFM) and spectroscopic ellipsometry. Phase identification of BaTiO3 and Ba0.8Sr0.2TiO3 was performed by XRD. XRD and Raman spectroscopy investigations demonstrate that thc Ba0.8Sr0.2TiO3 film exhibits tetragonal structure. AFM analysis demonstrates the elongated nanospherical particles on glass substrate and nanowires on silicon substrate, which represent a strong influence of the crystallinity of underlying substrate on the grain morphology in this technique. The thin films on both the substrates are uniformly coated without any pinhole to significant area (similar to 2.5 cm(2)), and this method might be extended to large area uniform coating. Spectroscopic ellipsometric measurements reveal the exact thickness, refractive index and extinction coefficient of the thin films.
Keywords: barium strontium titanate; barium titanate; dip coating; fabrication; ferroelectric material; large area coating; nanotechnology; thin film

Effect of aluminium doping on structural and gas sensing properties of zinc oxide thin films deposited by spray pyrolysis - Badadhe, Satish S.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2011)
A facile spray pyrolysis route is used to deposit aluminium doped ZnO (AZO) thin films on to the glass substrates. It is observed that on aluminium doping the particle size of ZnO reduces significantly; moreover, uniformity of particle also gets enhanced. Their XRD study reveals that intensity ratio of crystal planes depend on the aluminium doping concentration. The gas response studies of; similar to 800 nm thick Al-doped ZnO films at different operating temperatures show that 5 at% Al-doped ZnO thin film exhibits highest response towards H(2)S gas at 200 degrees C. The results suggest that the gas response strongly depends on the particle size and aluminium doping in the ZnO. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Aluminium; H(2)S sensor; Spray pyrolysis; thin film; Zinc oxide

Field emission studies of silver nanoparticles synthesized by electron cyclotron resonance plasma - Purohit, Vishwas; Mazumder, Baishakhi; Bhise, Ashok B.; Poddar, Pankaj; Joag, Dilip S.; Bhoraskar, S. V. (Applied Surface Science, 2011)
Field emission has been studied for silver nanoparticles (25-200 nm), deposited within a cylindrical silver target in an electron cyclotron resonance (ECR) plasma. Particle size distribution was controlled by optimum biasing voltages between the chamber and the target. Presence of non-oxidized silver was confirmed from the X-Ray diffraction analysis; however, thin protective layer of oxide was identified from the selective area electron diffraction pattern obtained with transmission electron microscopy. The silver nanoparticles were seen to exhibit hilly pointed like structures when viewed under the atomic force microscopy (AFM). The emissive properties of these particles were investigated by field emission microscopy. It is found that this technique of deposition is ideal for formation of nanoparticles films on different substrate geometries with size controllability as well as its application to emission devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cold plasma; field emission; Nanoparticles; thin film

Synthesis and characterization of chemically deposited nickel substituted CdSe thin film - Hankare, P. P.; Jadhav, B. V.; Chate, P. A.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2011)
The technologically important Cd(0.5)Ni(0.5)Se thin film has been developed by solution growth technique on non-conducting glass substrate in tartarate bath containing Cd(+2), Ni(+2) ions and sodium selenosulphate in an aqueous alkaline medium at room temperature. Various preparative conditions of the thin films are outlined. The films were characterized by X-ray diffraction, scanning electron microscope, optical absorption and electrical measurements. The X-ray diffraction study indicates that the film is polycrystalline in nature with hexagonal phase. Scanning electron micrograph shows that the film is homogeneous with well-defined grains. The films have high optical absorption coefficient. Thermoelectric power measurement shows p-type conduction mechanism. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Crystal growth; Electrical conductivity; thin film

Modification of crystal anisotropy and enhancement of magnetic moment of Co-doped SnO2 thin films annealed under magnetic field - Loya-Mancilla, Sagrario M.; Poddar, Pankaj; Das, Raja; Ponce, Hilda E. Esparza; Templeton-Olivares, Ivan L.; Solis-Canto, Oscar O.; Ornelas-Gutierrez, Carlos E.; Espinosa-Magaa, Francisco; Olive-Mendez, Sion F. (Nanoscale Research Letters, 2014)
Co-doped SnO2 thin films were grown by sputtering technique on SiO2/Si(001) substrates at room temperature, and then, thermal treatments with and without an applied magnetic field (H-TT) were performed in vacuum at 600 degrees C for 20 min. H-TT was applied parallel and perpendicular to the substrate surface. Magnetic M(H) measurements reveal the coexistence of a strong antiferromagnetic (AFM) signal and a ferromagnetic (FM) component. The AFM component has a N,el temperature higher than room temperature, the spin axis lies parallel to the substrate surface, and the highest magnetic moment m =7 mu(B)/Co at. is obtained when H-TT is applied parallel to the substrate surface. Our results show an enhancement of FM moment per Co+2 from 0.06 to 0.42 mu(B)/Co at. for the sample on which H-TT was applied perpendicular to the surface. The FM order is attributed to the coupling of Co+2 ions through electrons trapped at the site of oxygen vacancies, as described by the bound magnetic polaron model. Our results suggest that FM order is aligned along [101] direction of Co-doped SnO2 nanocrystals, which is proposed to be the easy magnetization axis.
Keywords: Antiferromagnetism; Crystal anisotropy; Diluted magnetic oxide; Ferromagnetism; Magnetic anisotropy; Magnetic moment; Spin axis; thin film

Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film

Method to form semiconductor quantum dot (QD) thin films by igniting a flame at air-liquid interface: CdS and WO3 - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Colloid and Interface Science, 2015)
We reveal an easy, inexpensive, efficient one step flame synthesis of semiconductor/metal oxide thin films at air-liquid interface, subsequently, transferred on suitable substrate. The method has been illustrated by the formation of CdS and Wo(3) QDs thin films. The features of the present method are (1) Growth of thin films consisting of 0.5-2.0 nm sized Quantum Dots (QDs)/(ultra-small nanoparticles) in a short time, at the air-liquid interface which can be suitably transferred by a well-known Blodgett technique to an appropriate substrate, (2) The method is suitable to apply layer by layer (LbL) technique to increase the film thickness as well as forming various compositions as revealed by AFM measurements. The films are characterized for their structure (SAED), morphology (TEM), optical properties (UV-Vis.) and photoluminescence (PL). Possible mechanism of formation of QDs thin film and effect of capping in case of COS QDs is discussed. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: CdS; Flame synthesis; interface; Quantum Dots (QDs); thin film; WO3

Highly transparent wafer-scale synthesis of crystalline WS2 nanoparticle thin film for photodetector and humidity-sensing applications - Pawbake, Amit S.; Waykar, Ravindra G.; Late, Dattatray J.; Jadkar, Sandesh R. (ACS Applied Materials & Interfaces, 2016)
In the present investigation, we report a one-step synthesis method of wafer-scale highly crystalline tungsten disulfide (WS2) nanoparticle thin film by using a modified hot wire chemical vapor deposition (HW-CVD) technique. The average size of WS2 nanoparticle is found to be 25-40 nm over an entire 4 in. wafer of quartz substrate. The low-angle XRD data of WS2 nanoparticle shows the highly crystalline nature of sample along with orientation (002) direction. Furthermore, Raman spectroscopy shows two prominent phonon vibration modes of E12g and A1g at similar to 356 and similar to 420 cm(-1), respectively, indicating high purity of material. The TEM analysis shows good crystalline quality of sample. The synthesized WS2 nanoparticle thin film based device shows good response to humidity and good photosensitivity along with good long-term stability of the device. It was found that the resistance of the films decreases with increasing relative humidity (RH). The maximum humidity sensitivity of 469% along with response time of similar to 12 s and recovery time of similar to 13 s were observed for the WS2 thin film humidity sensor device. In the case of photodetection, the response time of similar to 51 s and recovery time of similar to 88 s were observed with sensitivity similar to 137% under white light illumination. Our results open up several avenues to grow other transition metal dichalcogenide nanoparticle thin film for large-area nanoelectronics as well as industrial applications.
Keywords: chemical vapor deposition; humidity sensor; nanoparticle; photosensor; thin film; tungsten disulfide

Crack-free conjugated PbS quantum dot-hole transport layers for solar cells - Sharma, Ashish; Dambhare, V. Neha; Bera, Jayanta; Sahu, Satyajit; Rath, Arup K. (ACS Applied Nano Materials, 2021)
Colloidal quantum dots (QDs) benefit from solution-phase processing and band-gap tuning for their application in solar cell development. Today's QD solar cells rely on solid-state ligand exchange (SLE) to replace bulky oleic acid (OA) ligands with small 1,2-ethanedithiol (EDT) ligands to develop a conducting hole transport layer (HTL). High volume contraction in EDT conjugated QD films, however, leads to crack and porosity in the HTL, which is a major cause of concern for the device reproducibility and large-area solar cell development. We show that partial removal of the OA ligands in the solution phase reduces the volume contraction in solid films, thereby allowing the growth of crack-free QD films in the SLE process. The cleaning of QDs by repeated precipitation and redispersion using a protic methanol (MeOH) solvent helps with partial removal of the OA ligands, but it is detrimental to the electronic properties of QDs. We develop a one-step solution-phase partial ligand-exchange process using ammonium salts, which enable partial replacement of the OA ligands and passivation of the QD surface. Introduction of the facile partial ligand-exchange process eliminates the need for tedious and wasteful multiple cleaning steps with MeOH, while improving the photophysical properties of QDs. The advancement in QD processing helps to build crack-free, smooth, and conjugated QD films for their deployment as HTLs in solar cell development. Partial ligand exchange with NH4SCN leads to a 1.5 times increase in p doping and mobility over multiple MeOH-cleaned PbS QD films. HTLs developed using NH4SCN QDs show an improved photovoltaic performance to attain a 10.5% power conversion efficiency. Improvement in the depletion width and hole collection efficiency leads to a superior photovoltaic performance, as confirmed from experimental studies and one-dimensional solar cell capacitance simulation.
Keywords: Efficiency; ligand; polydispersity; quantum dot; solar cells; thin film

Facile, sustainable and unassisted plain water oxidation on Au/Ce0.9Ti0.1O2 nanorods in direct sunlight - Dubey, Anjani; Mishra, Abhaya Kumar; Negi, Sanjay Singh; Gopinath, Chinnakonda S. (Journal of Chemical Sciences, 2022)
Impressive rate of solar water oxidation to molecular oxygen (O-2) has been demonstrated on nanorods (NRs) of Ce0.9Ti0.1O2 (CT-NR) and Au-deposited CT-NR (Au-CT-NR) photocatalysts with a sacrificial agent (Fe3+) and in plain water in one sun condition, direct sunlight and with lambda >= 455 nm. Probably the highest 0 2 yield of 11 mmol/h.g was observed with Au-CT-NR thin film in plain water in direct sunlight, with no sacrificial agent or applied potential. Photoelectrochemical measurements demonstrate a marked reduction in oxidation onset potential of Au-CT-NR by 150 mV with stable photocurrent (0.75 mA/cm(2)), compared to CT-NR (0.23 mA/cm(2)), indicating the operative of plasmon-induced resonant energy transfer (PIRET) process. Effective electron quenching by nanogold and hence low recombination in the depletion region is a critical step for the observation of a high rate of oxygen evolution. In addition to this, a predominant change in the nature of the valence band from O-2p dominated on CeO2 to Ce-4f dominated with CT-NR (due to Ti4+ introduction in CeO2), the efficient light absorption of photocatalysts in thin-film form, functional and effective PIRET process, and facile E-F alignment, enhances the oxygen evolution with Au-CT-NR in direct sunlight and make it highly sustainable. A possible mechanism of water oxidation is proposed from the observed experimental findings.
Keywords: ceria; Electronic integration; Photocatalysis; thin film; water splitting

Tuning of work function of ZnO by doping and co-doping: an investigation using X-ray photoelectron spectroscopy - Soumya, K.; Selvam, I. Packia; Vinod, C. P.; Potty, S. N. (Thin Solid Films, 2022)
The shift in the work function of the ZnO thin film upon varying codoping ratio has been investigated by X-ray photoelectron spectroscopy. A notable shift of 0.2 eV in the work function was achieved in the films when the Al: In doping ratio was changed from 0:10 to 10:0. The elemental composition of the dopants obtained from XPS analysis showed the presence of more amount of In dopant than Al in codoped ZnO films. In this way a clear understanding of the variation in electrical properties on dopant ratio is obtained. A decrease in work function was also observed with the increase in free carrier concentration when the codopant ratio is changed. The effects of Burstein moss, band narrowing, and band renormalization observed in the bandgap were explained by an upward and downward shift of valence band maxima of the corresponding thin films. The controllable work function of the codoped ZnO films by varying the doping ratio offers excellent potential advantages in optoelectronic devices.
Keywords: Indium -Aluminum co -doping; Spray coating; thin film; Work function; X-ray photoelectron spectroscopy; Zinc oxide

Facile one-pot synthesis of Cu x O/TiO2 photocatalysts by regulating Cu oxidation state for efficient solar H2 production - Rajendran, Sivaraj; Mani, Sunesh S.; Nivedhitha, Thazhath R.; Asoka, Anantha Krishnan; Arun, Pushkaran S.; Mathew, Thomas; Gopinath, Chinnakonda S. (ACS Applied Energy Materials, 2023)
Development of highly efficient CuxO/TiO2 photocatalysts by regulating the oxidation state of Cu exclusively in either single or mixed oxidation state(s) is desirable but difficult to achieve without employing any external reagents. The present work describes a one-pot synthesis strategy to obtain CuxO/TiO2 photocatalysts with Cu in +1 and/or +2 by using a suitable combination of ethylene diamine tetra acetic acid (EDTA) and ethylene diamine, carefully varying the Cu content, and heat treatment process. CuxO/TiO2 nanocomposite catalysts were characterized thoroughly by physicochemical methods. Textural analysis indicates a high dispersion of CuxO on porous TiO2 with p-n heterojunctions between them in CuxO/TiO2 catalysts. UV-visible spectral analysis suggests the presence of CuxO on TiO2 with significantly extended absorption from the UV to the visible region. X-ray photoelectron spectroscopy (XPS) analysis indicates a strong synergetic interaction between TiO2 and CuxO due to the comparable CB potential and p-n heterojunction at the interface among them. Photoelectrochemical studies demonstrate excellent charge-carrier separation efficiency, low charge-transfer resistance, and high double-layer capacitance with Cu2O/TiO2 photocatalysts. Photocatalytic efficacy of a CuxO/TiO2 nanocomposite in thin-film form has been demonstrated for solar hydrogen generation in sunlight. The incorporation of Cu+ in TiO2 largely improves the H-2 production, and all of the CuxO/TiO2 nanocomposites in thin-film form exhibited higher efficiency compared to their particulate/suspension counterpart. Among the composite catalysts, TiCu-1 in thin-film form, with Cu exclusively in +1 oxidation state, exhibited a high hydrogen production rate of 7.06 mmol/hg, which is 6 times higher than its suspension counterpart; also catalysts containing mixed Cu-oxidation states exhibited about 60-70% activity as that of TiCu-1. The superior performance of Cu2O/TiO2 nanocomposites in thin-film form was due to their enhanced light harvesting ability, high mass transfer rate, and easy accessibility of the reactant species to the active sites.
Keywords: heterojunction; Photocatalysis; Solar hydrogen; thin film; titania

Influence of deposition potential on electrodeposited bismuth-copper oxide electrodes for asymmetric supercapacitor - Bobade, Rushikesh G.; Dabke, Niteen B.; Shaikh, Shoyebmohamad F.; Al-Enizi, Abdullah M.; Pandit, Bidhan; Lokhande, Balkrishna J.; Ambare, Revanappa C. (BATTERIES & SUPERCAPS, 2024)
Keywords: Bi2CuO4; Deposition Potential; Electrodeposition; supercapacitor; thin film

Multiphasic heterojunctions: a strategic approach to enhance the charge transfer dynamics of titania for superior solar photocatalytic hydrogen production - Ningthoukhongjam, Pujita; Gopinath, Chinnakonda S.; Nair, Ranjith G. (International Journal of Hydrogen Energy, 2025)
Multiphasic titania has been prepared to study the role of multiple heterojunctions on the charge transfer dynamics and resultant photocatalytic hydrogen production. Through an acid regulated hydrothermal method, four materials with following phase compositions were prepared viz. single phase anatase and rutile, biphasic anatase-rutile and triphasic anatase-brookite-rutile. The phase compositions of the materials were confirmed through XRD and HRTEM studies. The biphasic and triphasic materials were found to be highly nanoparticulate in nature while forming numerous and diverse heterojunctions. In the triphasic material, various binary and ternary heterojunctions were observed. These heterojunctions performed in harmony to ensure efficient charge transport as shown by the low charge transfer resistance and high electron lifetime. This subsequently ensured a high reduction capability and photocurrent response. This all culminated into the triphasic material outperforming all other materials in solar photocatalytic hydrogen production. The H2 yield from the triphasic material was 81% and 40% higher than the pristine anatase and the biphasic material respectively. Additionally, by using the triphasic material in thin film form, a 4-fold increase in the hydrogen yield with a high apparent quantum efficiency of 8.2 % was achieved over the particulate form. The superior charge transport and photocurrent response due to the greater varied heterojunction formation in the anatase-rutile-brookite material as opposed to that in the biphasic material led to this superior performance. Thus, multiple heterojunctions, in this case, a triphasic heterojunction of anatase, rutile and brookite phases opens up a new avenue of research for efficient green hydrogen production.
Keywords: Green hydrogen production; heterojunction; Photocatalysis; Photoelectrochemical analysis; thin film; titania